Becoming an Older Volunteer: A Grounded Theory Study. (12th December 2010) - Witucki Brown, Janet; Chen, Shu-li; Mefford, Linda; Brown, Allie; Callen, Bonnie; McArthur, Polly
Abstract : This Grounded Theory study describes the process by which older persons "become" volunteers. Forty interviews of older persons who volunteered for Habitat for Humanity were subjected to secondary content analysis to uncover the process of "becoming" a volunteer. "Helping out" (core category) for older volunteers occurs within the context of "continuity", "commitment" and "connection" which provide motivation for volunteering. When a need arises, older volunteers "help out" physically and financially as health and resources permit. Benefits described as "blessings" of volunteering become motivators for future volunteering. Findings suggest that older volunteering is a developmental process and learned behavior which should be fostered in older persons by personally inviting them to volunteer. Intergenerational volunteering projects will allow older persons to pass on knowledge and skills and provide positive role modeling for younger volunteers.